Automated radiosynthesis and preclinical evaluation of two new PSMA-617 derivatives radiolabelled via [18F]AlF2+ method - Marco Nicola Iannone; Silvia Valtorta; Stefano Stucchi; Stefano Altomonte; Elia Anna Turolla; Elisa Vino; Paolo Rainone; Valentina Zecca; Alessia Lo Dico; Marco Maspero; Mariangela Figini; Matteo Bellone; et al. (SpringerOpen, 2024)
Abstract Background In the last decade the development of new PSMA-ligand based radiopharmaceuticals for the imaging and therapy of prostate cancer has been a highly active and important area of research. The most promising derivative in terms of interaction with the antigen and clinical properties has been found to be "PSMA-617", and its lutetium-177 radiolabelled version has recently been approved by EU and USA regulatory agencies for therapeutic purposes. For the above reasons, the development of new derivatives of PSMA-617 radiolabelled with fluorine-18 may still be of great interest. This paper proposes the comparison of two different PSMA-617 derivatives functionalized with NODA and RESCA chelators, respectively, radiolabelled via [18F]AlF2+ complexation. Results The organic synthesis of two PSMA-617 derivatives and their radiolabelling via [18F]AlF2+ complexation resulted to proceed efficiently and successfully. Moreover, stability in solution and in plasma has been evaluated. The whole radiosynthesis procedure has been fully automated, and the final products have been obtained with radiochemical yield and purity potentially suitable for clinical studies. The biodistribution of the two derivatives was performed both in prostate cancer and glioma tumour models. Compared with the reference [18F]F-PSMA-1007 and [18F]F-PSMA-617-RESCA, [18F]F-PSMA-617-NODA derivative showed a higher uptake in both tumors, faster clearance in non-target organs, and lower uptake in salivary glands. Conclusion PSMA-617 NODA and RESCA derivatives were radiolabelled successfully via [18F]AlF2+ chelation, the former being more stable in solution and human plasma. Moreover, preclinical biodistribution studies showed that [18F]F-PSMA-617-NODA might be of potential interest for clinical applications.